2014
DOI: 10.5007/1980-0037.2014v16n6p714
|View full text |Cite
|
Sign up to set email alerts
|

Treinamento funcional: funcional para que e para quem?

Abstract: -The prescription of neuromuscular conditioning programs aimed at the development and maintenance of activities of daily living (ADLs) has been based on functionality. The functional training proposal needs further academic discussion. The present study presents a critical view on the functional training, assumptions, characteristics and definitions. The mere exercise selection does not make it a functional training, as there are no exercises that have greater or lesser functionality. For training to be functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 2 publications
0
8
0
12
Order By: Relevance
“…This new method is based on the application of a systematized program of integrated, multi-articular and multi-planar exercises aimed at improving movement ability, the strength of the CORE region, and neuromuscular efficiency for the specific needs of each individual. 8,9 With the application of a 12-weeks functional exercise circuit, Whitehurst et al 10 reported an improvement of 14% in flexibility, 8.4% in agility, 12.9% in balance, 7.4% in cardiorespiratory capacity, and 8.5 % in physical function of the elderly. Milton et al 11 applied a 12-week functional exercise intervention and showed an improvement of 43% in shoulder flexibility, 13% in agility/dynamic balance, 14% in upper body strength, 13% in lower body strength, and 7% in cardiorespiratory fitness, when compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…This new method is based on the application of a systematized program of integrated, multi-articular and multi-planar exercises aimed at improving movement ability, the strength of the CORE region, and neuromuscular efficiency for the specific needs of each individual. 8,9 With the application of a 12-weeks functional exercise circuit, Whitehurst et al 10 reported an improvement of 14% in flexibility, 8.4% in agility, 12.9% in balance, 7.4% in cardiorespiratory capacity, and 8.5 % in physical function of the elderly. Milton et al 11 applied a 12-week functional exercise intervention and showed an improvement of 43% in shoulder flexibility, 13% in agility/dynamic balance, 14% in upper body strength, 13% in lower body strength, and 7% in cardiorespiratory fitness, when compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Acréscimos na força e na potência muscular estão positivamente associados a reduções no risco de morte por qualquer causa (Brill, Macera, Davis, Blair, & Gordon, 2000;Ruiz et al, 2008) e ao desempenho funcional para as atividades da vida diária (Izquierdo et al, 1999;Hanson et al, 2009;Pereira et al, 2012;Cadore et al, 2014) Ultimamente, pode-se notar o direcionamento dos programas de treinamento neuromuscular para melhora da funcionalidade, a partir do uso de movimentos multiarticulares semelhantes às atividades cotidianas, visando demonstrar maior eficiência na melhora da capacidade funcional do indivíduo (Da SilvaGrigoletto, Brito & Heredia, 2014;Resen-deNeto, Da Silva-Grigoletto & Santos, 2016). Whitehurst, Johnson, Parker, Brown e Ford (2005), com uma intervenção de 12 semanas, aplicando um circuito de exercícios funcionais, mostraram melhora da flexibilidade (14,0%), da agilidade (8,4%), do equilíbrio (12,9%), da capacidade cardiorrespiratória (7,4%), e da função física (8,5%) de 119 idosos.…”
Section: Referênciasunclassified
“…Para isso, o TF utiliza exercícios multiarticulares e multiplanares, combinados a movimentos de aceleração, redução e estabilização, que tem como objetivo principal aprimorar a qualidade de movimento, melhorar a força da região da central do corpo (core) e a eficiência neuromuscular para as necessidades específicas do idoso (Da SilvaGrigoletto, Brito & Heredia, 2014;ResendeNeto, Da Silva-Grigoletto & Santos, 2016). Estudos recentes têm sugerido que esse tipo de intervenção pode, de fato, ter um efeito positivo sobre a aptidão funcional de idosos (Bouaziz et al, 2016), podendo, inclusive, ser mais eficiente que o treinamento de força tradicional (TT) (Liu, Shiroy, Jones & Clark, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Sabe-se que a obesidade está relacionada a diversos prejuízos na vida dos indivíduos 4 , interferindo também nas questões relacionadas ao aspecto funcional. A capacidade funcional está associada à capacidade para cumprir com eficiência as tarefas do dia a dia 5 . Um estudo avaliou a capacidade funcional de mulheres divididas em três grupos conforme sua classificação no índice de massa corporal (eutrófico, sobrepeso e obeso), sendo observado que as mulheres obesas apresentaram pior capacidade funcional em relação às demais 6 .…”
Section: Introductionunclassified